Energy system contribution during competitive cross-country skiing - Losnegard, T. (European Journal of Applied Physiology, 2019)
Energy system contribution during cross-country (XC) skiing races is dependent on several factors, including the race duration, track profile, and sub-techniques applied, and their subsequent effects on the use of the upper and lower body. This review provides a scientific synopsis of the interactions of energy system contributions from a physiological, technical, and tactical perspective. On average, the aerobic proportion of the total energy expended during XC skiing competitions is comparable to the values for other sports with similar racing times. However, during both sprint (= 1.8 km) and distance races (= 10 and 15 km, women and men, respectively) a high aerobic turnover interacts with subsequent periods of very high work rates at ~ 120 to 160% of VO2peak during the uphill sections of the race. The repeated intensity fluctuations are possible due to the nature of skiing, which involves intermittent downhills where skiers can recover. Thus, the combination of high and sustained aerobic energy turnover and repeated work rates above VO2peak, interspersed with short recovery periods, distinguishes XC skiing from most other endurance sports. The substantially increased average speed in races over recent decades, frequent competitions in mass starts and sprints, and the greater importance of short periods at high speeds in various sub-techniques, have demanded changes in the physiological, technical, and tactical abilities needed to achieve world-class level within the specific disciplines.